The Routledge companion to Shakespeare and religion - Stockton, William (Routledge literature companions, 2026)
"The Routledge Companion to Shakespeare and Religion surveys new and longstanding critical conversations about the role of religion in Shakespeare's plays and poems. It features thirty-four chapters authored by leading scholars on topics from antitheatricality and humanism to race and trans theology. Arranged by keyword, this volume includes entries on major religions and religious movements, including Judaism, Islam, Catholicism, and Calvinism. Contributors consider Shakespeare's interpretation of scripture and later treatments of his plays as a kind of scripture. They also explore religious themes in Shakespeare's works, including repentance, reconciliation, toleration, and conversion. Guided by what's often called the 'turn to religion' in Renaissance studies, the Companion does not attempt to pin a religious identity on Shakespeare. Instead, it examines how Shakespeare took up, for his own theatrical purposes, the many religious conflicts of the English Renaissance world. Providing a useful starting point for learning about the relationship between Shakespeare's art and religion, each chapter assumes a minimum of background information and concludes with a list of further reading for those interested in pursuing topics further. This authoritative yet accessible collection is the go-to resource for anyone studying Shakespeare, early modern literature, and literature and religion"-- Provided by publisher